ECONOMIC ANALYSIS OF INTERNATIONAL LAW: ISSUES OF METHODOLOGY - R. B. Sadykova (Московский журнал международного права, 2019)
INTRODUCTION. The article is devoted to the methodology of economic analysis of international law which is a new approach to the study of international law. Its methodology has not been substantively explored in Russian scholarship of international law. Meanwhile, the economic dimension of international law has practical and theoretical perspectives according to the predominant opinion in foreign doctrines of international law.MATERIALS AND METHODS. The article is based on legal and economic doctrines of both Russian and foreign scholars. The methods used in the course of this study include general methods (analysis, synthesis, induction, deduction) and specific methods (the methods of formal logic, legal history). Methods of economic theory such as the method of positive analysis and the method of scientific abstraction are also used.RESEARCH RESULTS. The article explores the differences between legal and economic approaches. The basic categories and theories of economic analysis, such as rationality, externalities, transaction costs are revealed. The methodology is presented through the discussion of the main assumptions: the analogy between interstate system and economic market; rationality assumption with regard to the subject of international law, which can be considered as a unitary, collective or corporate actor.DISCUSSION AND CONCLUSIONS. Economic analysis of international law is intended to complement traditional methods of conducting legal research. The article highlights the basic economic theories and categories of economic analysis of international law, which allow Russian scientists to start studying one of the most popular theoretical approaches in foreign scholarship.